2001
DOI: 10.1073/pnas.061028198
|View full text |Cite
|
Sign up to set email alerts
|

The use of mRNA display to select high-affinity protein-binding peptides

Abstract: We report the use of ''mRNA display,'' an in vitro selection technique, to identify peptide aptamers to a protein target. mRNA display allows for the preparation of polypeptide libraries with far greater complexity than is possible with phage display. Starting with a library of Ϸ10 13 random peptides, 20 different aptamers to streptavidin were obtained, with dissociation constants as low as 5 nM. These aptamers function without the aid of disulfide bridges or engineered scaffolds, yet possess affinities compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
223
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(230 citation statements)
references
References 38 publications
4
223
0
3
Order By: Relevance
“…First, further developments are needed in the re-targeting of these selfish genes to novel host sequences, though important progress has been made, both by design and by selection (Segal et al 1999;Guo et al 2000;Buchholz & Stewart 2001;Wilson et al 2001;Chevalier et al 2002;Santoro & Schultz 2002;Seligman et al 2002;Takahashi & Fujiwara 2002). Second, it must be demonstrated that these elements can be made to work in the prospective target species: insects, for example, are natural hosts only for the LINE-like elements.…”
Section: Prospectsmentioning
confidence: 99%
“…First, further developments are needed in the re-targeting of these selfish genes to novel host sequences, though important progress has been made, both by design and by selection (Segal et al 1999;Guo et al 2000;Buchholz & Stewart 2001;Wilson et al 2001;Chevalier et al 2002;Santoro & Schultz 2002;Seligman et al 2002;Takahashi & Fujiwara 2002). Second, it must be demonstrated that these elements can be made to work in the prospective target species: insects, for example, are natural hosts only for the LINE-like elements.…”
Section: Prospectsmentioning
confidence: 99%
“…To date, display techniques employing such principles as phage display [7,8], ribosome display [9,10], yeast display [11], covalent display [12], mRNA display [13,14], and other conceptually analogous methodologies [15,16] profoundly impact the way novel drugs are discovered, yielding new and more efficacious classes of therapeutic agents (e.g., antibody drug conjugates) [17,18]. DNA-encoded library technology aims to extend the realm and the potential of these display approaches to the en masse interrogation of small synthetic organic molecules.…”
Section: A New Solution For An Old Problem: Finding a Needle In The Hmentioning
confidence: 99%
“…Each streptavidin monomer binds one biotin molecule with femtomolar affinity, one of the strongest non-covalent interactions observed in nature [8]. Over the past 15 years several groups have developed peptide binders to the tetrameric streptavidin protein [9][10][11][12][13] and a variety of protein engineering approaches have been applied to tailor affinity for specific applications [14][15][16]. This provides a simple and clean system for protein purification as a streptavidin binding peptide can be selectively eluted from a streptavidin affinity column using appropriate concentrations of biotin.…”
mentioning
confidence: 99%
“…Consequently, several groups have set out to find higher affinity alternatives to the Strep-tags [9,13]. Using a mRNA display library,…”
mentioning
confidence: 99%
See 1 more Smart Citation